2010
DOI: 10.3201/eid1604.090500
|View full text |Cite
|
Sign up to set email alerts
|

Porcine-Origin Gentamicin-ResistantEnterococcusfaecalisin Humans, Denmark

Abstract: During 2001–2002, high-level gentamicin-resistant (HLGR) Enterococcus faecalis isolates were detected in 2 patients in Denmark who had infective endocarditis and in pigs and pork. Our results demonstrate that these isolates belong to the same clonal group, which suggests that pigs are a source of HLGR E. faecalis infection in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 11 publications
2
59
0
2
Order By: Relevance
“…Few studies have shown the existence of clonal relationship between clinical isolates of E. faecalis. In this line, Larsen et al [52] found HLGR E. faecalis ST16 with similar PFGE types, isolated from pigs, pork, nonhospitalized humans and patients with endocarditis. In the present research, the clonal type EFA-A isolates were distributed among food and human samples (minced meat, abdominal fluid and hemoculture).…”
Section: Discussionmentioning
confidence: 60%
“…Few studies have shown the existence of clonal relationship between clinical isolates of E. faecalis. In this line, Larsen et al [52] found HLGR E. faecalis ST16 with similar PFGE types, isolated from pigs, pork, nonhospitalized humans and patients with endocarditis. In the present research, the clonal type EFA-A isolates were distributed among food and human samples (minced meat, abdominal fluid and hemoculture).…”
Section: Discussionmentioning
confidence: 60%
“…Exchange of resistant strains among different ecosystems is less probable due to the supposed ecovar association, especially among hospital-associated E. faecium strains (see chapter 5), although dissemination across host barriers of vancomycin-and multi-resistant enterococci was described anecdotally, especially for the less strongly host-adapted E. faecalis strains (Manson et al, 2003a;Manson et al, 2003b;Manson et al, 2004;Agerso et al, 2008;Larsen et al, 2010;Hammerum et al, 2010;Freitas et al, 2011a). Vancomycin resistance among enterococci most probably spreads via a dissemination of mobile genetic elements of variants of the vanA-type element Tn1546 mostly located on mobilizable or conjugative plasmids (Sletvold et al, 2007;Novais et al, 2008;Sletvold et al, 2008;Freitas et al, 2009;Rosvoll et al, 2009;Sletvold et al, 2010;Laverde Gomez et al, 2011;Werner et al, 2011b;Freitas et al, 2011b).…”
Section: Localization and Spread Of Vana-and Vanb-type Resistancementioning
confidence: 99%
“…Strains from human-adapted clonal complexes (CCs) causing most enterococcal infections may eventually be recovered from farm and companion animals (e.g., E. faecium clonal complex 17 [CC17] and E. faecalis CC2), and strains from CCs commonly found among animals have also been isolated from humans (E. faecium CC5, E. faecalis sequence type 16 [ST16], or E. faecalis CC21) (4,9,13,14,28,53). Documented cases of animal-human VRE transmission frequently involve healthy humans in close interaction (farming or petting) with animals, but most of these studies do not provide molecular characterization of either clones or their subcellular genetic elements (1,3,10,17,26,28,31,33), despite the comprehensive epidemiological studies of Tn1546 (vanA) and Tn5382 (vanB) (8,24,38,52,54).…”
Section: Vre Isolates From Pigs (N ‫؍‬mentioning
confidence: 99%